An Efficient Data Transmission by using Modern USB Flash Drive - B.Naresh Kumar Reddy; N. Venktram; Sireesha Sireesha (Institute of Advanced Engineering and Science, 2014)
Now a day’s Electronics plays a vital role in our daily life. It is a key in making this world a small and making everything happen at our finger tips, today’s most used and flexible is USB flash drives, which is used to store the data and data transfer between them related with computer, and we are not able to share files between two USB flash drives when user is away from computer. So to overcome this problem we are designing a complete blend of hardware and software With the help of this project we can not only transfer the data but also we can see the transfer of the particular file which we want to send by using LCD display. In our proposal we are transferring the data between two USB flash drives using two ways. One is Wireless Technology either Wi-Fi technology which we can send/receive File or Bluetooth Technology which we can send/receive data to USB flash drive with Bluetooth enabled devices like Mobiles, laptops etc.. Another is in-built USB slots to perform data transmission to other pen drives directly without the use of the computer system. The implementation of an operating system and a processor to the USB Flash drive are the main challenges in this proposed system.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6577